HUBUNGAN TEKANAN DARAH DENGAN KADAR KOLESTEROL LDL(Low Density Lipoprotein) PADA PENDERITA PENYAKIT JANTUNG KORONERDI RSUP.Dr.M.DJAMIL PADANG - ERAWATI ERAWATI (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Coronary heart disease is a disease caused by narrowing of the coronary arteries of the heart. This happens because of its high cholesterol levels can cause atherosclerosis in blood vessels Hypercholesterolemia mainly occurs when increased production of LDL (Low Density Lipoprotein). As a result of the narrowing of blood vessels blood flow to the heart will be disrupted, causing symptoms of chest pain that is a typical symptom of coronary heart disease. Chronic atherosclerosis can cause blood flow to the heart to be disturbed, so that the left ventricle must pump stronger to produce enough force to push blood through the atherosclerotic vascular system that can lead to increased systolic and diastolic blood pressure resulting in hypertension. This study included descriptive analytic research using cross sectional approach, is dependent variable (incidence of coronary heart disease) and indenpendent variable (blood pressure and LDL cholesterol level) collected at the same time. The study was conducted on September 10, 2016 - April 4, 2017 at the Central Laboratory and Heart Ward RSUP.Dr. M. Djamil Padang. The sampling technique used is purposive sampling, that is the technique of determining the sample with certain consideration. Of 36 samples of patients with coronary heart disease (CHD) showed a correlation between systolic blood pressure with LDL cholesterol level has a value of 0.585> 0.05 which states there is a moderate relationship between the two variables, and has significant significance of 0.00 <0, 05 and Ha are received. The correlation between diastolic blood pressure and LDL levels has a value of 0,507> 0,05 which states there is a moderate relationship between the two variables, and has significant value of 0.02 significance <0.05 and Ha is accepted. Based on these results then there is a significant relationship between blood pressure with LDL cholesterol levels in the blood.